2011
DOI: 10.1093/jnci/djq529
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Evidence-Based Information on Cancer Prevention to State-Level Policy Makers

Abstract: Our results suggest that taking a "one-size-fits-all" approach when delivering information to policy makers may be less effective than communicating information based on the type of policy maker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
138
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(147 citation statements)
references
References 66 publications
5
138
2
2
Order By: Relevance
“…This work was part of a study designed to increase the dissemination of evidence-based interventions to control cancer, focusing on the uptake of effective environmental and policy approaches among statelevel policymakers [6]. To better understand quantitative data collected in the study's first phase and to address study research questions, the research team decided to conduct a set of key-informant interviews with state legislators.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This work was part of a study designed to increase the dissemination of evidence-based interventions to control cancer, focusing on the uptake of effective environmental and policy approaches among statelevel policymakers [6]. To better understand quantitative data collected in the study's first phase and to address study research questions, the research team decided to conduct a set of key-informant interviews with state legislators.…”
Section: Methodsmentioning
confidence: 99%
“…Linking research evidence to direct impacts, costs and benefits has been identified as a facilitator to incorporating evidence into policy, whereas low quantity, quality, accessibility and usability of evidence are known barriers [5][6][7][8][9]. Other barriers to the inclusion of research in the policymaking process include differences in decision making (between researchers and policymakers), poor timing, ambiguous findings, information overload and lack of relevant data [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 An effective policy brief has been described as one that makes the evidence concise and understand able; explains why the evidence is important; and describes evidence-informed policy options that would be suitable actions for policy-makers to take. [29][30][31] With a problem clarified in a policy brief, what is known and not known about the options clearly described, and key implementation considerations clearly flagged, policy-makers may be more readily able to identify viable ways forward. 28 It is pertinent to state that despite the existence and importance of effective evidence-packaging mechanisms such as policy briefs in the promotion of EIP, most policymakers particularly in LMICs lack the capacity to develop and use them.…”
Section: Introductionmentioning
confidence: 99%